Ionic co-aggregates (ICAs) based oral drug delivery: Solubilization and permeability improvement - Xianzi Zheng; Zhezheng Fang; Weizi Huang; Jianping Qi; Xiaochun Dong; Weili Zhao; Wei Wu; Yi Lu (Elsevier, 2022)
Due to the overwhelming percentage of poorly water-soluble drugs, pharmaceutical industry is in urgent need of efficient approaches for solubilization and permeability improvement. Salts consisting of lipophilic fatty acid anions and hydrophilic choline cations are found to be surface active and able to form ionic co-aggregates (ICAs) in water. Choline oleate-based ICAs significantly enhance oral absorption of paclitaxel (PTX) as compared with cremophor EL-based micelles (MCs). Aggregation-caused quenching probes enable tracking of intact ICAs in in vivo transport and cellular interaction. Prolonged intestinal retention of ICAs than MCs implies stronger solubilizing capability in vivo. Ex vivo imaging of major organs and intestinal tracts suggests transepithelial transport of intact ICAs. Cellular studies support the enhanced absorption of PTX and transmembrane transport of intact ICAs. In conclusion, ICAs, consisting of lipophilic ions and hydrophilic counter-ions, are of great potential in delivery of poorly water-soluble drugs by enhancing solubility and permeability.